Acknowledgements Vol.1 - Pahari, Narayan Prasad (Nepal Journal of Mathematical Sciences, 2020)
The Editorial Board would like to express their sincere gratitude and special thanks to the following reviewers for their substantial contribution of time and expertise to the journal’s rigorous editorial process for this volume, regardless of whether the papers are finally accepted /published or not. Golam Mortoja, Vidyasagar University, West Bengal, India Dipesh Barman, IIEST Shibpur, Kolkata, West Bengal, India Dil Bahadur Gurung, Kathmandu University, Nepal Amarendra Mishra, Patna University, Patna, India Shambhu Sharma, Dayalbagh Educational Institute, Agra, India Ram Prasad Khatiwada, Tribhuvan University, Nepal Durga Jang KC, Tribhuvan University, Nepal Parameshwari Kattel, Tribhuvan University, Nepal Khurram Shabbir, Department of Mathematics GC University, Lahore, Pakistan Gede Adhitya Wisnu Wardhana, Universitas Mataram, Indonesia Lakshmi Narayan Mishra, School of Advanced Sciences, Vellore Institute of Technology, Tamil Nadu, India B. Gandhi, BVM Engineering College, Vallabh Vidyanagar, Gujarat, India Lekhnath Bhattarai, Tribhuvan University, Nepal Prakash Upadhyay, Tribhuvan University, Nepal Shankar Prasad Khanal, Tribhuvan University, Nepal Eka Ratna Acharya, Tribhuvan University, Nepal Vinod Parajuli, Tribhuvan University, Nepal Debendra Banjade, Coastal Carolina University , USA